2021
DOI: 10.15690/pf.v18i4.2301
|View full text |Cite
|
Sign up to set email alerts
|

Implications of the COVID-19 Pandemic for Pediatric Primary Care Practice in Europe

Abstract: .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Evidence has shown diverse experiences of guardians, however, with negative experiences common everywhere wherein guardians were accessing care for children under five years. Most evidence from elsewhere showed that there was unavailability of medications in most facilities, and guardians were made to go and buy from pharmacists, which made guardians reluctant to use healthcare facilities [6,7]. Some studies showed that guardians were dissatisfied with the attitudes of nurses and healthcare workers in some facilities whilst receiving under five childcare services [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence has shown diverse experiences of guardians, however, with negative experiences common everywhere wherein guardians were accessing care for children under five years. Most evidence from elsewhere showed that there was unavailability of medications in most facilities, and guardians were made to go and buy from pharmacists, which made guardians reluctant to use healthcare facilities [6,7]. Some studies showed that guardians were dissatisfied with the attitudes of nurses and healthcare workers in some facilities whilst receiving under five childcare services [8,9].…”
Section: Introductionmentioning
confidence: 99%